Unpacking the influence of parental and peer support on youth financial literacy and saving behavior in Indonesia - Putra, Ivan Gumilar Sambas (Jurnal Siasat Bisnis, 2025)
Purpose – This study investigates the Influence of parental and peer connections on Financial Literacy and saving Behavior among Indonesian youth. It examines how social agents shape financial competence and explores the mediating role of financial Literacy and the moderating role of self-control in enhancing saving habits.Design/methodology/approach – A quantitative research design was used a cross-sectional online survey. Data were collected from 350 students enrolled in applied colleges across Indonesia. Constructs such as Financial Literacy, self-control, saving Behavior, and social influences were measured using confirmed multi-item Likert scales. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. Bootstrapping with 5,000 resamples was conducted to test the significance of direct, indirect, and moderating effects.Findings – The findings reveal that both parental and peer influences significantly enhance youth financial literacy, which positively affects saving Behavior. Financial Literacy mediates the relationships between social impact and saving Behavior. Self-control positively moderates the effect of financial Literacy on saving Behavior, suggesting that individuals with higher self-discipline are more likely to translate financial knowledge into saving practices.Research limitations/implications – The study’s reliance on self-reported data and a purposive sample of applied college students may limit the generalizability of the results. However, the findings emphasize the need for integrated financial education programs that involve families and peer groups, as well as behavioral training to strengthen self-regulation.Originality/value – This research contributes to the limited body of literature on youth saving Behavior in emerging economies by showing the interplay between social influences, Financial Literacy, and self-control. It offers theoretical insights based on Social Learning Theory and the Behavioral Life Cycle Theory, as well as practical recommendations for designing culturally relevant financial literacy programs for youth.